2002
DOI: 10.1111/j.1540-8183.2002.tb01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Retrieval of a Wallstent from the Pulmonary Artery Following Stent Migration from the Iliac Vein

Abstract: Wallstents are being used increasingly in conjunction with balloon dilatation for treatment of iliac vein stenosis. Stent misplacement or migration is a complication of the procedure, and may be symptomatic and warrant repositioning or removal. We report the case of a patient whose iliac vein stenosis was managed with two overlapping Wallstents and was complicated by embolization of one stent into the right ventricle (RV) and the other to the pulmonary artery (PA). This article illustrates percutaneous endovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…[2][3][4][5][6] Despite problems associated with compression and puncture of intra-shunt stents described later in the article, short-and mid-term patency rates are comparable to other locations of peripheral venous stent placement. Patency rates at the venous anastomosis tend to be lower than other sites.…”
Section: Stent Placement In Peripheral Venous Stenosesmentioning
confidence: 88%
See 1 more Smart Citation
“…[2][3][4][5][6] Despite problems associated with compression and puncture of intra-shunt stents described later in the article, short-and mid-term patency rates are comparable to other locations of peripheral venous stent placement. Patency rates at the venous anastomosis tend to be lower than other sites.…”
Section: Stent Placement In Peripheral Venous Stenosesmentioning
confidence: 88%
“…4 Finally, the most serious complication of peripheral stent placement is the migration of peripheral venous stents to the right atrium, right ventricle, and pulmonary arteries. 6 The use of self-expanding stents and the practice of overestimating the diameter of the vein when choosing stent size may minimize the risk of this serious complication. 7 Treatment of Angioplasty-Induced Rupture Interventional radiologists should be familiar with those situations in which significant morbidity can result from delaying treatment with stents.…”
Section: Stent Placement In Peripheral Venous Stenosesmentioning
confidence: 99%
“… 1 Therefore, only a few exceptional cases of stent migration after iliofemoral vein stenting have been reported. 4 5 More frequently, cases of venous stent migration have been reported for the nutcracker syndrome whereby a smaller stent is placed in the left renal vein. 6 One case of a 55-year-old woman ended fatally after transvenous migration of an infrarenal inferior vena cava stent into the right atrium and through the intraatrial septum due to ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only few cases with venous stent migration into the heart and fatal ending are reported so far and no case with open-heart surgery. 4 5 …”
Section: Introductionmentioning
confidence: 99%
“…Those findings were not present in this case, as the FB was a tube with a patent lumen, as documented by Doppler ultrasonography, thus rendering the patient asymptomatic 4 . As there was no clinical indication of the FB location, a thorough scanning with arterial vascular ultrasound was recommended, a method that has already been used in some situations to detect intra-arterial FBs, especially in studies analyzing stents that had migrated from their original sites [5][6][7] . In the specialized medical literature consulted by the authors, no case report was found in which abdominal, pelvic and lower limb scanning was used to detect a temporary shunt that had migrated to a more distal artery.…”
Section: Discussionmentioning
confidence: 99%